ОПТИМІЗАЦІЙНИЙ ПІДХІД ДО ВИЗНАЧЕННЯ КОНСТРУКТИВНИХ ПАРАМЕТРІВ ЛІНІЙНОГО МАГНІТОЕЛЕКТРИЧНОГО ДВИГУНА ВІБРАЦІЙНОЇ ДІЇ - Бондар, Р.П. (Інститут електродинаміки НАН України, Київ, 2022)
The constructional parameters of the linear permanent magnet vibratory motor in accordance with the set optimization criteria (minimum cost, force to volume ratio and efficiency) and mechanical load parameters are substantiated in the work. To do this, a computer model was developed, which is based on magnetic and electrical equivalent circuits with lumped parameters. The magnetic circuit of the model is built taking into account the saturation of the magnetic material, magnetic losses and leakage fluxes. The electromagnetic force amplitude of the motor is determined on the basis of the fundamental component of the Fourier series expansion of the air-gap flux density. The mechanical part of the model is constructed using the electromechanical analogy method, according to which, induced armature EMF is represented by a voltage drop on the equivalent mechanical resistance. The problem of choosing the constructional parameters for the given mechanical load characteristics is considered in conjunction with the nonlinear connections of the system and subject to thermal, magnetic and electrical constraints. Using the gradient descent method, the motor parameters were optimized and the most effective designs that meet the selected criteria were determined. References 8, figures 5, tables 2.